Tingkat Pendidikan dan Status Ekonomi Pemilik Hewan Kesayangan dalam Hal Pengetahuan dan Penerapan Kesejahteraan Hewan (EDUCATION LEVEL AND ECONOMIC STATUS OF PET OWNERS ON KNOWLEDGE AND ANIMAL WELFARE IMPLEMENTATION) - Rahmiati, Dwi Utari; Pribadi, Eko Sugeng (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
Pet is an animal that lives to partially or completely dependent on humans for a particular purpose.Keep a pet as a companion animal, should pay attention to animal welfare. This study aims to gain insightabout the relationship between education level and economic status of pet owners on knowledge andimplementation of the animal welfare principles. The data were collecting by direct interview or a face toface interview to the animal clinic or hospital visitors on site (accidental technique). The data were calculatedby statistical methods chi square to examined the relationship or the impact of the two nominal variablesand measure the strengthness of the relationships between variables with each other nominal variables.Data showed a significantly correlation between the economic status of n North Jakarta respondentsbehavior (p value is 0.040), with the economic status of the Central Jakarta respondents’ attitudes (pvalue is 0.020), level of education and attitude of South Jakarta respondents (p value is 0.000). There wereno difference significantly between the level of education and economic status of the respondents’ knowledgewas observed in all study sites. However, based on current information and on site observation, NorthJakarta and West Jakarta respondents were considered to be able to demonstrate more sufficientknowledge of the animal welfare principles.
Keywords: animal welfare, economic status, education level